Selfies as Duplex Non-verbal Communication: Human—Media Interaction, Human—Human Interaction, Case Study, and Research Manifesto - Bruno, Nicola; Uccelli, Stefano; Pisu, Veronica; Belluardo, Mauro; De Stefani, Elisa (Frontiers in Computer Science, 2020)
Using conceptual tools from semiotics, proxemics, and sensorimotor neuroscience, we propose a duplex model for understanding selfies as non-verbal communication involving an interplay between two layers of interaction: human - media (semiotically primary) and human - human (secondary). We suggest that this approach has promise as a tool for understanding this newborn form of human social behavior and its social, psychological, and neural underpinnings. To support our claim, we do several things. We offer a definition of selfies and outline our model. We review the existing literature on selfies as non-verbal communication to show that there is evidence bearing on our theoretical framework. We present a case study documenting how a combination of image analysis and kinematic measurement can be used to compare taker - smartphone interactions during selfie-taking with image features that play a role in the virtual interaction between the selfie-taker and his or her viewers. Our results support the feasibility of our approach and reveal a sex-related effect on the composition of selfies matching a related difference in the kinematic markers that describe the taker - smartphone interaction. Finally, we discuss outstanding questions in understanding selfies as duplex non-verbal communication and conclude by inviting further research on this topic.